Impact Of Agriculture Land Conversion On Walfare Conditions Of Farmers In Pattallassang District Gowa Regency - Fahri Faknan (Pustaka Digital Indonesia, 2023)
The research objective to be achieved is to determine the impact of agricultural land conversion on the welfare condition of the farming community in Pattallassang District, Gowa Regency. This type of research is a type of qualitative research, this research was conducted using a qualitative descriptive analysis method. The analysis leads to a detailed and in-depth description. This type of research is also a research method that focuses on a particular case to be observed and analyzed carefully to completion. The case in question can be in the form of individuals or groups. If you look at the economic conditions of the people affected by the land conversion, most of the people admit that after the land conversion that occurred in their area, the economy will also increase because with the development, the field will indirectly increase. work is also open to people who previously did not have jobs and also to local communities who take advantage of this by opening a business. Ministry of Agrarian Spatial Planning/National Land Agency Perform technical considerations if the owner of the power of attorney of the land to be converted makes an application to the relevant local government then apply for a permit at the relevant regional PTSP, after the permit from the PTSP is issued, the ATR/BPN will conduct a review of the land to be converted.